Population-Based Study of Docetaxel or Abiraterone Effectiveness and Predictive Markers of Progression Free Survival in Metastatic Castration-Sensitive Prostate Cancer - Briones, Juan; Khan, Maira; Sidhu, Amanjot K.; Zhang, Liying; Smoragiewicz, Martin; Emmenegger, Urban (Frontiers in Oncology, 2021)
ABSTRACT Background Both Docetaxel (DOC) and Abiraterone (ABI) improve the survival of men with metastatic, castration sensitive prostate cancer (mCSPC). However, the outcome amongst mCSPC patients is highly variable, while there is a lack of predictive markers of therapeutic benefit. Furthermore, there is limited data on the comparative real-world effectiveness of adding DOC or ABI to androgen deprivation therapy (ADT). Methods We conducted a retrospective analysis of 121 mCSPC patients treated at Odette Cancer Centre (Toronto, ON, Canada) between Dec 2014 and Mar 2021 (DOC n=79, ABI n=42). The primary endpoint studied was progression free survival (PFS), defined as the interval from start of ADT to either (i) biochemical, radiological, or symptomatic progression, (ii) start of first-line systemic therapy for castration-resistant prostate cancer (CRPC), or (iii) death, whichever occurred first. To identify independent predictive factors for PFS in the entire cohort, a Cox proportional hazard model (stepwise selection) was applied. Overall survival (OS) was amongst secondary endpoints. Results After a median follow-up of 39.6 and 25.1 months in the DOC and ABI cohorts, respectively, 79.7% of men in the DOC and 40.5% in the ABI group experienced a progression event. PFS favored the ABI cohort (p=0.0038, log-rank test), with 78.0% (95%CI 66.4-91.8%) of ABI versus 67.1% (57.5-78.3%) of DOC patients being free of progression at 12 months. In univariate analysis superior PFS was significantly related to older age at diagnosis of mCSPC, metachronous metastatic presentation, low-volume (CHAARTED) and low-risk (LATITUDE) disease, ≥90% PSA decrease at 3 months (PSA90), and PSA nadir 0.2 at 6 months. Age (HR=0.955), PSA90 (HR=0.462) and LATITUDE risk stratification (HR=1.965) remained significantly associated with PFS in multivariable analysis. OS at 12 months was 98.7% (96.3-100%) and 92.7% (85.0 – 100%) in the DOC and ABI groups (p=0.97), respectively. Conclusions In this real-world group of men undergoing treatment intensification with DOC or ABI for mCSPC, we did not find a significant difference in OS, but PFS was favoring ABI. Age at diagnosis of mCSPC, PSA90 at 3 months and LATITUDE risk classification are predictive factors of PFS in men with mCSPC.